2021
DOI: 10.3390/ijerph18157901
|View full text |Cite
|
Sign up to set email alerts
|

Access to Healthcare for Migrant Patients in Europe: Healthcare Discrimination and Translation Services

Abstract: Background: Discrimination based on ethnicity and the lack of translation services in healthcare have been identified as main barriers to healthcare access. However, the actual experiences of migrant patients in Europe are rarely present in the literature. Objectives: The aim of this study was to assess healthcare discrimination as perceived by migrants themselves and the availability of translation services in the healthcare systems of Europe. Methods: A total of 1407 migrants in 10 European Union countries (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Participants in our sample reported lacking awareness of such strategies or misjudged their rights, with many mistakenly believing they lacked entitlement. Notably, we found that those with medical cover, registered with a GP, or who had recourse to the healthcare system, were more likely to access vaccination, in line with prior work on COVID-19 [27, 29] and other conditions [28]. Misinformation due to rumours, and defiance towards authorities reinforce these barriers, and are well-known in PEH [22, 23, 24, 27, 28, 29, 30].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Participants in our sample reported lacking awareness of such strategies or misjudged their rights, with many mistakenly believing they lacked entitlement. Notably, we found that those with medical cover, registered with a GP, or who had recourse to the healthcare system, were more likely to access vaccination, in line with prior work on COVID-19 [27, 29] and other conditions [28]. Misinformation due to rumours, and defiance towards authorities reinforce these barriers, and are well-known in PEH [22, 23, 24, 27, 28, 29, 30].…”
Section: Discussionsupporting
confidence: 84%
“…Notably, we found that those with medical cover, registered with a GP, or who had recourse to the healthcare system, were more likely to access vaccination, in line with prior work on COVID-19 [27, 29] and other conditions [28]. Misinformation due to rumours, and defiance towards authorities reinforce these barriers, and are well-known in PEH [22, 23, 24, 27, 28, 29, 30].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Asylum seekers are excluded from the Health Insurance Act and receive care through a parallel health system, with a central financial reimbursement policy for healthcare providers who provide services for undocumented migrants. While this policy ensures the availability of healthcare services for this group, it does not necessarily equate to adequate utilization of these services [ 59 – 61 ]. For example, the translation services have been defunded in an effort for cost-containment and to stimulate integration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be interpreted from a structural and organisational point of view to delivering healthcare, given the way in which they intersect with multiple factors, including individuals’ legal status, resettlement, length of stay, and stress accessing healthcare resources. Studies have found that remoteness of a settlement, perceived discrimination in terms of benefits and healthcare entitlements, accessing resources, including social and language supports, public transport and employment, might worsen healthcare provision for people from refugee backgrounds [ 18 , 46 , 47 ]. According to Ziersch and colleagues, discrimination has been attributed to adverse impacts on the mental health of people from refugee backgrounds in Australia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%